2015
DOI: 10.1155/2015/895803
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Visual Symptomatology Associated with Refractive, Accommodative, and Binocular Anomalies

Abstract: Purpose. To characterize the symptomatology of refractive, accommodative, and nonstrabismic binocular dysfunctions and to assess the association between dysfunctions and symptoms. Methods. 175 randomised university students were examined. Subjects were given a subjective visual examination with accommodative and binocular tests, evaluating their symptomatology. Accommodative and binocular dysfunctions (AD, BD) were diagnosed according to the number of existing clinical signs: suspect AD or BD (one fundamental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 65 publications
7
42
4
1
Order By: Relevance
“… 9 , 12 , 28 , 29 The asthenopic symptoms can be diverse, ranging from chronic blurred vision, headache, eyestrain, reading difficulties, visual fatigue, sleepiness, loss of comprehensionand movement of print, to avoidance of reading and other close work. 30 – 33 …”
Section: Methodsmentioning
confidence: 99%
“… 9 , 12 , 28 , 29 The asthenopic symptoms can be diverse, ranging from chronic blurred vision, headache, eyestrain, reading difficulties, visual fatigue, sleepiness, loss of comprehensionand movement of print, to avoidance of reading and other close work. 30 – 33 …”
Section: Methodsmentioning
confidence: 99%
“…These dysfunctions challenge near‐activity demands. Symptoms may include blurred vision, reading problems, headache, diplopia, and in many cases, difficulty in maintaining comfortable vision for a long time . Also, these visual disorders are associated with musculoskeletal discomfort in the neck and shoulder .…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that uncorrected astigmatic students showed difficulty in stimulating an accurate accommodative response [ 11 ]. However, Cacho-Martínez et al observed that although accommodative dysfunction was associated with increased visual symptoms in a sample of university students, the effect is eliminated when analyses adjusted for uncorrected refractive error [ 12 ]. In addition, Dwyer and Wick observed that vergence or accommodative anomalies present in patients with uncorrected ametropia can often be alleviated after a period of spectacle wear [ 13 ].…”
Section: Introductionmentioning
confidence: 99%